KEPEMIMPINAN KRISTEN DALAM BUDAYA PATRIARKIMengeksplorasi Narasi Terhadap Figur Pemimpin Perempuan Dalam Alkitab Seperti Debora, Ester, Miryam Sebagai Landasan Servant Leadership - Damaris Rumba; Firdayanti Talle’; Lita Bungan; Meriati Tudang; Risa Pangari (Jurnal Salome : Multidisipliner Keilmuan, 2025)
This study examines the figures of female leaders in the Bible, such as Deborah, Esther, and Miriam, as the foundation for the concept of "Servant Leadership" introduced by Robert K. Greenleaf. The research aims to explore how these figures exercised their leadership amidst a dominant patriarchal culture and to elaborate on the relevance of their leadership values in applying the principles of Servant Leadership within a Christian context. Using qualitative research methods that are exploratory and interpretative in nature, this study focuses on analyzing Biblical texts to uncover the narratives of female leadership and their contributions to shifting the patriarchal cultural paradigm in the church and modern society. The findings reveal that the leadership values of these Biblical female figures, such as courage, wisdom, humility, and service to the community, align with the principles of Servant Leadership, which prioritize meeting others' needs, fostering a sense of community, and leading with integrity. In addition to providing theological contributions, these leadership narratives can also serve as an inspiration for building a more inclusive and egalitarian paradigm in the church and society.